The Environmental Factors Enhance the Growth and Survival of Rhizophora Seedlings - Sinaga, Na Dame Maulibulung; Pradipta, Aruna; Martuti, Nana Kariada Tri; Jabar, Muhammad Abdul; Soleha, Iro Datus (Biosaintifika: Journal of Biology & Biology Education, 2025)
Coastal ecosystems are synonymous with mangrove trees. Threatened mangrove existence is tantamount to reduced biological existence, weakened coastal protection, and reduced carbon storage. Moreover, mangrove growth naturally depends on the quality of seedlings supported by proper nursery management. This study aims to evaluate the impact of four environmental factors (light intensity, salinity, pH, and tidal frequency) on the growth and survival of Rhizophora: Rhizophora mucronata, Rhizophora stylosa, and Rhizophora apiculata cultivated in nurseries with a water system integrated with the Internet of Things (IoT). A single-factor design was applied, with each treatment bed containing 600 seedlings (200 per species) and an uncontrolled bed as a control. Weekly random sampling of 20% of seedlings from each treatment for eight weeks. Data were analyzed using a two-way ANOVA with treatment and species as fixed factors, followed by the Tukey HSD test at a significance level of 5%. The results showed that R. mucronata in the light treatment (without shade net) achieved the highest survival rate (98.8%) and the largest stem diameter, which was 0.698 cm. In addition, the highest seedling height was R. mucronata in the high-yield salinity treatment, reaching 56.78 cm, and the highest number of leaves was recorded in R. apiculata in the salinity treatment, with an average of 6.92 leaves per seedling. IoT-integrated nurseries stabilize water supply and tidal cycles, reduce mortality to below 10%, and enhance seedling quality. These findings indicate that nursery environmental management can improve the consistency of mangrove seedling growth and support large-scale restoration.